UPAYA MENDAPATKAN AGENS BIOKONTROL PENYAKIT PENYAKIT LAYU TOMAT FUSARIUM OXYSPORUM F.SP. LYCOPERSICI MELALUI EKSPLORASI DAN UJI POTENSI PGPR ISOLAT BAKTERI PSEUDOMONAS SPP. - Widnyana, I Ketut (Bumi Lestari, 2011)
In this experiment the rhizosphere of several plants were explored to obtain Pseudomonas spp. A total of ninety soil samples were collected from rhizosphere of maize, peanuts, tomatoes, peppers, squash vines, ferns, onions, kale, and vanilla in all districts and cities of Bali Island.Bacteria were isolated from the rhizosphere soil using a culture media namely, King B agar. King B agar allows the production of fluoresceine (or pyoverdin), a yellow-green pigment that fluorescens under ultraviolet light in certain strains of Pseudomonas. Twenty-two Pseudomonas isolates that produced characteristic pigment from light green to bluish green in the media were obtained. The twenty-two isolates were KB1, KB2, KB4, KB16, KB19, KB24, KB29, KB30, KB32, KB33, KB34, KB36, KB46 KB49, KB61, KB67, KB68, KB69, KB71, KB77, KB78, and KB80. The bacterial isolates were further tested for pathogenicity using tobacco as an indicator plant. Twelve Pseudomonas isolates KB1, KB16, KB19, KB24, KB32, KB33, KB34, KB36, KB49, KB61, KB69 and KB77 were pathogenic while ten isolates KB2, KB4, KB29, KB30, KB46, KB67, KB68, KB71, KB78 and KB80 were non-phatogenic. This result will be subsequently used for evaluation of the induction of resistance in vanilla. Based on the results of the evaluation of isolates as a biological control potential with PGPR (Plant Growth Promoting Rhizobacteria), the isolates from Pseudomonas KB2, KB68 and KB 80 were shown to have the capability to increase growth of indicator plants 14% higher than controls. The study indicated that Pseudomonas were potent as biological control for Fusarium oxysporum F.SP, lycopersici that wilt disease of tomato.
Keywords: exploration; isolation; Pseudomonas spp.; petogenicity; PGPR